The Concept of Development: Heuristic Turns. From Economic Growth to The Rights Approach - Millán Valenzuela, Henio (Sociedad y Economía, 2023)
The concept of development has changed over time, reflecting different theories and approaches to the problem of human welfare. This article aims to present and analyze these changes, which can be seen as heuristic turns: shifts in perspective that offer new ways of understanding and addressing the issue of development. The methodology used is a review of the most significant turning points in the history of development thinking. The result is a distinction between three main perspectives: the view of development as a process of economic growth and convergence; the view of development as a response to the challenges of underdevelopment and heterogeneity; and the view of human rights as a normative framework for development. The first two perspectives focus on the mechanisms that enable or hinder development, while the third one tries to define what development means in terms of human dignity and well-being, and how to design public policies that promote it.